Big Data Analysis of Threat Intelligence Based on IP. Issue 3 (April 2021) - Xu, Fajian; Chen, Shuzhen
Abstract: This paper first discusses the concept of network threat intelligence and related resource integration, and proposes a three-tier architecture model of threat intelligence analysis system based on IP. Then, it discusses the diversified data acquisition technology, information index extraction technology, data mining and data modeling analysis technology, the key technology of threat intelligence credible intelligence analysis model based on machine learning and privacy protection. Finally, this paper considers and summarizes the legal standardization of threat intelligence analysis.